2016
DOI: 10.3311/ppso.8486
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tax Education in a Business School: a Case Study

Abstract: Tax legislation affects the business and social environment in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…The research study carried out by Mohd Yusofamong academicians within the Universiti Teknologi MARA and Baykan and Cekalso conformed that there was less than moderate tax knowledge among academicians (Mohd Yusof, Safeei, & Lee, 2022) and (Baykan & Cek, 2019). Belchova and Sobotovicova also supports that taxpayers completed tax-focused subjects had better understanding than those who had not completed (Belchova & Sobotovicova, 2016).Mohd Yusofet. al furthermore conformed that formal tax education should be implemented at the university level for uplifting tax knowledge level of taxpayers by incorporating Malaysian and Indonesian colleges and universities in the study (Mohd Yusof N. A., Safeei, Chuen, & Novita, 2022).An empirical research by Said reported that there was an increase number in tax knowledge before and after the delivery of the material in the classroom (Said, 2018).…”
Section: Resultsmentioning
confidence: 76%
“…The research study carried out by Mohd Yusofamong academicians within the Universiti Teknologi MARA and Baykan and Cekalso conformed that there was less than moderate tax knowledge among academicians (Mohd Yusof, Safeei, & Lee, 2022) and (Baykan & Cek, 2019). Belchova and Sobotovicova also supports that taxpayers completed tax-focused subjects had better understanding than those who had not completed (Belchova & Sobotovicova, 2016).Mohd Yusofet. al furthermore conformed that formal tax education should be implemented at the university level for uplifting tax knowledge level of taxpayers by incorporating Malaysian and Indonesian colleges and universities in the study (Mohd Yusof N. A., Safeei, Chuen, & Novita, 2022).An empirical research by Said reported that there was an increase number in tax knowledge before and after the delivery of the material in the classroom (Said, 2018).…”
Section: Resultsmentioning
confidence: 76%
“…Di sisi lain, menurut penelitian yang dilakukan Blechová dan Sobotovičová menyatakan bahwa lebih dari 50% penduduk di negara yang diteliti, termasuk para mahasiswa hanya mendapatkan mata kuliah pengantar pajak saja sehingga untuk memahami pajak perlu dilakukan pendidikan perpajakan. Oleh karena itu, ini menunjukkan bahwa pengetahuan pajak secara tidak langsung meningkatkan kepatuhan pajak, karena keseluruhan mahasiswa dengan mendapatkan sebuah pendidikan pajak mampu membangun dan meningkatkan pengetahuan pajak, sedangkan mahasiswa yang tidak diajarkan pendidikan pajak tidak memiliki pengetahuan pajak atau hanya mengetahui pendidikan perpajakan yang rendah (Blechová and Sobotovičová 2016).…”
Section: Pendahuluanunclassified
“…Finally, the work carried out in the Czech Republic by [50] mentioning that we must face frequent changes in tax legislation and the state's approach to tax policy when teaching them at the tertiary level, worrying about the level of knowledge of students in these subjects. In their results, they obtain that the extracurricular students have the best results regarding the level of knowledge in the subject, exposing that a factor that influences this fact is that the majority of the extracurricular students already have a job.…”
Section: Learning About Tax Mattersmentioning
confidence: 99%